THE EFFECT OF TOTAL ASSETS, PROFITABILITY, LIQUIDITY AND THE BOARD OF COMMISSIONERS ON CORPORATE SOCIAL RESPONSIBILITY (Empirical Study on Banking in Indonesia) DISCLOSURES - Kurnia Heriansyah; Wuri Haryanti (Sean Institute, 2023)
This study aims to determine how much influence of company size/asset, profitability, liquidity and board of commissioners effect on corporate social responsibility disclosure of banks listed on Indonesia Stock Exchange in 2016-2019. The analysis was performed using independent variables that company size, profitability, liquidity and board of commissioners, while the dependent variable used is corporate social responsibility disclosure. This type of research is quantitative by using secondary file. The population in this study is a banks listed on Indonesia Stock Exchange in 2016-2019 with a population of 39 banks. The method of selecting sample using purposive sampling and obtained samples as 25 banks. The results of study explain that company size and profitability has no effect on corporate social responsibility disclosure, meanwhile, liquidity and board of commissioners positively and significantly effect on corporate social responsibility disclosure